Review of Facilities for Low-Income Countries : Supplement 1. (Policy Papers; Policy Paper, 2012)
This supplement aims to assess the economic impact of the Fund's support through its facilities for low-income countries (LICs). It relies on two complementary econometric analyses: the first investigates the longer-term impact of Fund engagement-primarily through successive medium-term programs under the Extended Credit Facility (ECF) and its predecessors (and more recently the Policy Support Instrument (PSI))-on economic growth and a range of other indicators and socio-economic outcomes; the second focuses on the role of IMF shock-related financing-through augmentations of ECF arrangements and short-term and emergency financing instruments-on short-term macroeconomic performance. The empirical results shed some light on two channels through which different Fund facilities may have helped LICs respond to the global financial crisis-(i) by supporting a gradual buildup of macroeconomic buffers in the decades prior to the crisis and (ii) by providing liquidity support at the height of the crisis. The combination of strong pre-crisis buffers and crisis financing allowed LICs to pursue counter-cyclical policy responses that preserved spending and facilitated a rapid recovery.